Characterization of reconstructed human skin containing Langerhans cells to monitor molecular events in skin sensitization. (February 2018) - Bock, Stephanie; Said, André; Müller, Gerrit; Schäfer-Korting, Monika; Zoschke, Christian; Weindl, Günther
Abstract: Human cell-based approaches to assess defined key events in allergic contact dermatitis (ACD) are well-established, but lack cutaneous penetration and biotransformation as well as cellular cross-talk. Herein, we integrated in vitro -generated immature MUTZ-3-derived Langerhans-like cells (MUTZ-LCs) or monocyte-derived LC-like cells (MoLCs) into reconstructed human skin (RHS), consistent of a stratified epidermis formed by primary keratinocytes on a dermal compartment with collagen-embedded primary fibroblasts. LC-like cells were mainly localized in the epidermal compartment and distributed homogenously in accordance with native human skin. Topical application of the strong contact sensitizer 2, 4-dinitrochlorobenzene (DNCB) induced IL-6 and IL-8 secretion in RHS with LC-like cells, whereas no change was observed in reference models. Increased gene expression of CD83, PD-L1, and CXCR4 in the dermal compartment indicated LC maturation. Importantly, exposure to DNCB enhanced mobility of the LC-like cells from epidermal to dermal compartments. In response to the moderate sensitizer isoeugenol and irritant sodium dodecyl sulphate, the obtained response was less pronounced. In summary, we integrated immature and functional MUTZ-LCs and MoLCs into RHS and provide a unique comparative experimental setting to monitor early events during skin sensitization. Highlights: Reconstructed human skin (RHS) with LCs shows normal epidermal differentiation. LCs incorporated into RHS resemble hallmarks of cutaneous LC morphology. Exposure to sensitizers augments cytokine release in LC-RHS. 2, 4-Dinitrochlorobenzene increases LC mobility in RHS.